The level of anti-(GalNAc beta) and anti-para-Forssman disaccharide igg antibodies in patients with gastrointestinal cancer: relation to survival - Smorodin, E.P.; Kurtenkov, O.A.; Sergeyev, B.L. (Experimental Oncology, 2013)
Serum anti-(GalNAc beta) and anti-para-Forssman disaccharide (PFdi, GalNAc beta1 - 3GalNAc beta) IgG levels were earlier found to be related to histological grading and progression of gastrointestinal cancer. Aim - to study the relation of serum antibodies level to survival in patients with gastrointestinal cancer. Methods: The level of anti-GalNAc beta, and PFdi IgG was analysed in the serum of patients with gastric (n = 78) and colorectal (n = 48) cancers in the long-term follow-up using ELISA with polyacrylamide glycoconjugates. Survival rate and hazard ratio (HR) were assessed by the Kaplan - Meier method and Cox univariate analysis in different pathomorphological groups. Better survival was observed in patients with an increased preoperative level of GalNAc beta antibodies. These were the gastrointestinal group in stages II, III or tumors T2 - 4 (n = 90 - 104, P = 0,007, HR = 0,48 - 0,49, 95 % CI 0,27 - 0,83, and the group with gastric cancer in stages I, II (n = 49, P = 0,051, HR = 0,39, 95 % CI 0,14 - 1,04). The survival time was significantly longer in the gastrointestinal group in patients whose GalNAc beta antibodies level rose in dynamics (stage III or N1 - 2: P = 0,031 - 0,039, HR = 0,29 - 0,31, 95 % CI 0,09 - 1,00). No significant difference in survival of patients was observed in the evaluation of PFdi antibodies. We suggest that the level of antibodies and its change reflect the enteric microbiota colonization, which may influence cancer progression via different interrelations between microbiota, the tumor and immune system. Key Words: gastrointestinal cancer, survival, GalNAc beta and para-Forssman disaccharide antibodies, enteric bacteria.